Neoadjuvant Toripalimab for Renal Cell Carcinoma: A Systematic Review - Rananda, Arif; Haikal, Vikri; Oktavian, Puguh; Setyobudi, David; Kristanto, Roy Dwi Antariksa (Green Publisher Indonesia, 2025)
Toripalimab, a programmed cell death protein-1 (PD-1) inhibitor, has emerged as a promising immunotherapy for renal cell carcinoma (RCC). This systematic review consolidates current evidence on the efficacy and safety of toripalimab-based regimens in RCC management. A systematic review was conducted following PRISMA guidelines and a pre-registered protocol (PROSPERO: CRD42021274404). Multiple databases and trial registries were searched from February 23, 2025. Six studies, including randomized controlled trials (RCTs), case-control studies, and case reports, were included for qualitative synthesis. The analysis demonstrated that toripalimab, particularly in combination with axitinib, significantly improved clinical outcomes compared to standard therapies like sunitinib. One major RCT reported a significant improvement in progression-free survival (PFS) (median 18.0 vs. 9.8 months) and a higher objective response rate (ORR) (56.7% vs. 30.8%). The combination also reduced the risk of disease progression or death by 35% (HR 0.65; 95% CI 0.49–0.86) and showed a significant overall survival (OS) benefit (HR 0.61; 95% CI 0.40–0.92). Favorable responses were also observed in challenging subgroups, including elderly patients and those with sarcomatoid RCC. Adverse events were consistent with known profiles of PD-1 and VEGFR inhibitors, including hypertension, hepatic enzyme elevation, and fatigue, and were generally manageable. Toripalimab-based regimens, especially in combination with axitinib, demonstrate significant improvements in PFS, ORR, and OS for patients with RCC, with a manageable safety profile. These findings support its potential as a valuable therapeutic option. However, further large-scale, multi-center studies with longer follow-up are warranted to confirm these findings.